Paradigma Baru Pembelajaran Al-Qur’an: Analisis Metode Bhatatsa Di Pesantren Alam Sayang Ibu - Nurmaidah (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This study examines the BHATATSA Method (Read, Memorize, Tadabbur, Write, and Act) as a new paradigm in Quranic learning at the Alam Sayang Ibu Islamic Boarding School. Developed by Jamaludin, the founder of PAMSI, this method is designed to complement the tahsin and tahfiz approaches with tafhim (understanding), resulting in a comprehensive and contextual learning process. BHATATSA emphasizes keyword analysis, inspirational writing, and concrete actions as a form of internalization of Quranic values ​​in the lives of students. This study uses a qualitative approach with a case study design, involving direct observation, in-depth interviews, and documentation of Quranic Diary activities. Data were collected from the founder, teachers, and students, and analyzed descriptively and qualitatively through the stages of condensation, presentation, and drawing conclusions. Validity was maintained through triangulation. The findings indicate that the BHATATSA method combines learning principles from Islamic heritage such as the theory of Sufyan bin Uyainah and Bloom's taxonomy, which each emphasize the stages of reading, understanding, memorizing, practicing, and disseminating. These five stages are adapted into activities that engage the five senses plus two: the heart and the mind, making learning more lively and reflective. This method has been tested for five years on digital platforms and four years in educational institutions. The results demonstrate that BHATATSA is able to improve Quranic literacy, develop critical thinking, and strengthen the role of Islamic boarding schools (pesantren) as adaptive and transformative Islamic educational institutions in the modern era.